FORMULASI SEDIAAN KRIM EKSTRAK BIJI KAKAO (Theobroma cacao) SEBAGAI ANTIBAKTERI Propionibacterium acne - Siti Nurjanah; Nopiyansyah Nopiyansyah; Ira Dwi Rahmawati (Fakultas MIPA Universitas Tulang Bawang Lampung, 2019)
Cocoa bean is one part cocoa plant which has many benefit in the health field. Polyphenolic compounds cocoa bean proven to have activity antioxidants and antibacterial. This research purposes to prove that cocoa bean extract (Theobroma cacao) could be formulated become cream preparation and had antibacterial activity against Propionibacterium acne. In this research cocoa bean extract formulated in cream preparation with different extract concentration such as, F1 (3%), F2 (6%) and F3 (12%) with using stearic acid, paraffin liquid, adepslanae, as oil phase, TEA, aquadest as water phase, and methyl paraben as preservative. Then that were evaluated of homogenity, organoleptic, pH, viscosity dispersive power, glutinous power and inhibition power of antibacterial. Result of evaluation of stock had a pH range of between 6,4-8,1, the viscosity range from 2324-526 cps 1, dispersive power between 5,47-6,95 cm, and the glutinous power between 4,2-5,3 second. Each formula was stable in storage cycling testand temperature 40ºC ± 2ºC, 28ºC ± 2ºC, 4ºC ± 2ºC and the three formulas had antibacterial of Propionibacterium acne. The conclusion of this study is cocoa bean extract could be formulated in cream preparations and had a zone of inhibition against bacteria Propionibacterium acne. Keywords: Antibacterial cream, Propionibacterium acne, Theobroma cacao